Words in the wilderness : critical literacy in the borderlands - Brown, Stephen Gilbert, 1949- (State University of New York Press, 2000)
Reflecting and building upon his time teaching on an Athabascan Indian reservation in Alaska, Brown (writing, U. of Tampa) attempts to incorporate his experience and the theories of Freire and other critical pedagogists into a work which recommends a resistance pedagogy for colonized and oppressed peoples. He relates his own transformation from a unwitting tool of the colonizer to someone who learned from his students what works in engaging "border" students education, throughout relating the material to current theoretical radical pedagogy.
Keywords: Brown, Stephen Gilbert, -- 1949-; Athapascan Indians -- Education -- Alaska.; Critical pedagogy.; Literacy.; Teachers -- Alaska -- Biography.; Educational Status; Athapascan -- Éducation -- Alaska.; Pédagogie critique.; Alphabétisation.; Enseignants -- Alaska -- Biographies.; literacy.; BIOGRAPHY & AUTOBIOGRAPHY -- Educators.; EDUCATION -- Students & Student Life.; Athapascan Indians -- Education; Critical pedagogy; Literacy; Teachers; Alaska; Biographies